Adaptive Control of Structures with MR Damper - Cetin, Saban; Zergeroglu, Erkan; Sivrioglu, Selim; Yuksek, Ismail (IEEE, 2009)
In this study, an adaptive control scheme is designed for vibration isolation of SDOF structural system using a semi-active MR (magnetorheological) damper. The main goal of using a MR damper system is for structural protection against earthquake excitation and wind loading. A structural system excited by an earthquake and controlled by using MR damper is modeled as a semi-active controlled, seismically excited and a nonlinear system with SDOF. A nonlinear observer is used to estimate of the unmeasurable internal state variable. Unknown parameters of MR damper are obtained by adaptation rules. The necessary input voltage to MR damper so as to generate desired damping force is derived by the adaptive control. Finally, response of semi-actively controlled building is obtained by simulation.
Keywords: SEISMIC RESPONSE REDUCTION; MAGNETORHEOLOGICAL DAMPERS; SEMIACTIVE CONTROL; FLUID DAMPERS; ALGORITHMS; FRICTION; STRATEGY; SYSTEMS; MODEL; Automation & Control Systems; Computer Science